Social Aspects in Novel ‘Jilbab Traveler: Love Sparks in Korea’ by Asma Nadia (Sociology of Literature) - Maghfiroh, Afi; Resdianto Permata Raharjo (Jurnal Disastri (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2024)
The research entitled Social Aspects of the Novel Jilbab Traveler Love Sparks in Korea by Asma Nadia (Literary Sociology) aims to describe social aspects using Wellek &; Warren's theory of literary sociology. The research method used by researchers is a qualitative descriptive method using literature review, note taking and interviews. The data used are quotes and texts on the objects studied, which explain the sociology of literary works. The data source used by researchers for this research is the novel Jilbab Traveler Love Sparks in Korea by Asma Nadia, as well as references to journal articles, proceeding articles, and others. The data collection technique that the researcher used was reading the novel carefully. Data analysis was carried out using objective hermeneutics, namely giving meaning to the quotes studied and recording them. Researchers conducted this research by identifying, introducing, categorizing, describing and analyzing the social aspects contained in the novel Jilbab Traveler Love Sparks in Korea by Asma Nadia based on Wellek &; Warren's literary theory. The results of the research prove that the social aspect in Wellek &; Warren's literary sociology theory which focuses on the sociology of literary works has a positive meaning, which can be implemented in life, namely religion and education.